Analysis of Determinants of Audit Delay in Trade, Service and Investment Companies in the Covid-19 Pandemic (Empire Study on the Indonesia Stock Exchange) - Linda Grace Loupatty; Theresia Febiengry Sitanala; Alfrin Ernest Marthen Usmany (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to empirically prove the factors that influence the occur-rence of audit delays for companies in the trade, services and investment sectors during the COVID-19 pandemic. The research was conducted at the Indonesia Stock Exchange, where the dependent variables are Return on Assets (ROA), Debt to Total Asset Ratio (DAR), company size and KAP reputation. And the independent variable is audit delay. This research is qualitative research using secondary data in the form of an annual report in 2020. The da-ta analysis method uses multiple regression. And the research results show that Return On Assets (ROA) has a significant effect on audit delay. Meanwhile, Debt to Total Asset Ratio (DAR), Firm Size and KAP Reputation have no significant effect on audit delay.